Combination of Bonding, Bridging and Linking Social Capital in a Livelihood System: Nomadic Duck Herders Amid the Covid-19 Pandemic in South Sulawesi, Indonesia - Salman, Darmawan; Kasim, Kasmiyati; Ahmad, Asmita; Sirimorok, Nurhady (Forest and Society, 2021)
Livelihood systems of nomadic duck herders make a unique study subject due to the livelihood assets, strategies, and outcomes they manage, which involve interactions with various actors that keep moving around. Social capital the duck herders build in their interaction with other actors, namely rice farmers, play an important role to face different vulnerability context, including those brought by the Covid-19 pandemic. This study aims to characterize components of bonding, bridging and linking social capital in the context of relationships between duck herders and other actors, and seeks to find the essential role of the combination of the three types of social capital for livelihood outcomes, particularly in facing vulnerabilities due to the pandemic. The method of grounded theory research was applied for its ability to allow researchers to reveal processual relationships between duck herders and other actors. Data were collected through semi structured interviews, analyzed by open, axial, and selective coding. The duck herders combine components of bonding, bridging, and linking social capital selectively depending on the interests behind each interaction with different actors. The bridging and linking role that social capital plays in herders’ interactions with farmers and irrigation officials is undertaken in order to gain access to natural capital (rice fields and irrigated water), while in their interaction with egg traders, they utilize bridging social capital to gain access to financial capital (in the form of cash and loans). The vulnerability context due to the pandemic has shaken the livelihood system of the duck herders by upsetting the egg supply chain due to social restriction policies. Social capital therefore plays an important role in facing vulnerability, in the context of forming good will among egg traders that continued to buy eggs from the duck herders, which served as a kind of pay back for the loyalty of the duck herders. We find that social capital plays a vital role in a livelihood system, within which the access to livelihood assets depend on social relations. This study also explored the impact of the Covid-19 pandemic as it resonates more on supply chains than production processes.